Biological Activities of Resveratrol against Cancer - Kim, Soo Mi; Kim, Sung Zoo (My University, 2018)
Resveratrol (RSV) is a polyphenolic compound naturally found in grapes, peanuts, and berries. Considerable research has been performed to determine the benefits of RSV against various human diseases, especially cancer. Despite numerous studies on the effect of RSV on cancer, correct understanding of its mechanism is still far from certainty. This review summarizes the recent results on the molecular mechanisms and pathways of actions of RSV against major cancers. According to investigations accomplished worldwide, RSV targets pathways such as cell cycle progression, autophagy, apoptosis, angiogenesis and invasion/metastasis to attenuate cancer progression mediated through PI3K/Akt/mTOR, Wnt, ROS, NF-κB, BAX/Bcl-2, AMPK, ERK, MAPK signaling pathway. Considering the sideeffects and data of clinical trials, RSV can be used for its maximum benefits in human diseases. Available published data provide strong clues on the impact of RSV on cancer management.
Keywords: Resveratrol; Gastric cancer; Esophageal cancer; Breast cancer; Lung cancer; Colon cancer